Bicycle handlebar injuries in children : findings on CT abdomen of 3 cases - Che Mohamed, Siti Kamariah; Abd. Aziz, Azian; Hassan, Radhiana; Sa'at@Yusof, Azlin; G , Krishna Kumar (2010)
Introduction Blunt abdominal injuries in children caused by bicycle handlebar are often difficult to diagnose, and the severity of the underlying injury may not be realized during the initial patient admission to the Emergency Department. High index of suspicion with proper radiologic evaluation can help identify presence of internal injuries. This will lead to appropriate and timely treatment.